2007
DOI: 10.1007/s10350-006-0872-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Technical Factors on Outcome of Restorative Proctocolectomy for Familial Adenomatous Polyposis

Abstract: Restorative proctocolectomy in patients with familial adenomatous polyposis has good functional outcomes and an acceptable rate of complications, which are independent of choice of technique. Handsewn ileoanal anastomosis with mucosectomy seems to reduce the incidence of subsequent neoplasia in the anal transitional zone but does not eliminate the risk of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…reported such risk as 10% at 7 years after hand‐sewn IPAA with mucosectomy. Furthermore, another study revealed that development of cancer was not different between the two anastomotic techniques 30. In light of these findings, all patients with FAP should undergo endoscopic surveillance at regular intervals regardless of the anastomotic procedure.…”
Section: Discussionmentioning
confidence: 89%
“…reported such risk as 10% at 7 years after hand‐sewn IPAA with mucosectomy. Furthermore, another study revealed that development of cancer was not different between the two anastomotic techniques 30. In light of these findings, all patients with FAP should undergo endoscopic surveillance at regular intervals regardless of the anastomotic procedure.…”
Section: Discussionmentioning
confidence: 89%
“…9,46,[50][51][52] Our group has personally witnessed one case that represent 3.8% of our RPC cases. 9 Another source of concern for FAP patients is the development of ileostomy carcinomas.…”
Section: Discussionmentioning
confidence: 97%
“…The rate of 47.6% of our patients who had at least one episode of pouchitis and our pouch failure rate of 7.6% are both in accordance with other long-term follow-up studies on IPAA for ulcerative colitis. 8,12,17,21,35,[42][43][44][45] The very low rate of local septic complications in our series probably results from various technical aspects: One reason might be the preservation of the mesorectal fat by performing the rectal dissection close to the bowel wall. This results in a small funnel-like cavity in which the pouch sits more tightly in the pelvis than after total mesorectal excision.…”
Section: Discussionmentioning
confidence: 92%
“…They range between 0% and 12.6% in a series in which patients with FAP were included, exclusively. [33][34][35] For studies in which only or predominantly patients with inflammatory bowel diseases were included, the leakage rates are somewhat higher, ranging between 2.7% and 15%. 1,7,19,36,37 Other local septic complications are pelvic abscesses without anastomotic leakage, fistulas, and pouch necroses.…”
Section: Discussionmentioning
confidence: 98%